2010
DOI: 10.4097/kjae.2010.58.6.514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anesthesia on fluid volume kinetics after infusion of colloid solution during blood donation

Abstract: BackgroundThe fluid kinetics of intravenously infused colloid during inhalation anesthesia and hemorrhage have not been investigated. We therefore assessed fluid space changes during infusion of hydroxyethyl starch solution after hemorrhage in conscious and desflurane-anesthetized individuals.MethodsFollowing the donation of 400 ml of blood, 500 ml of hydroxyethyl starch solution was infused over 20 minutes into wakeful and desflurane-anesthetized volunteers. Blood was repeatedly sampled to measure hemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, we could not adopt the two-volume model to explain the plasma dilution induced by administration of colloid solutions. In previous studies, the volume kinetics of colloid solutions were also described through the one-volume model 2,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we could not adopt the two-volume model to explain the plasma dilution induced by administration of colloid solutions. In previous studies, the volume kinetics of colloid solutions were also described through the one-volume model 2,19 .…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, a volume kinetic experiment in volunteers undergoing euvolaemic haemodilution with hydroxyethyl starch found that the elimination rate constant from central to peripheral fluid compartments was not reduced, as is the case for ISS, but increased during anaesthesia compared with awake subjects. 98 The duration of resuscitation attributable to hydroxyethyl starch after removal of a unit of blood was therefore shorter in subjects during desflurane anaesthesia.…”
Section: Plasma Substitutesmentioning
confidence: 97%
“…This is supported by findings indicating less early fluid extravasation in anesthetized compared to non-anesthetized patients receiving equal crystalloid volume loads [ 16 ]–[ 18 ], presumably due to vascular relaxation and concomitant lower perfusion pressures rather than choice of anesthetic agent [ 19 ]. In contrast, the degree of fluid extravasation following FFP infusion is largely unknown, but results from similar experiments using artificial colloids suggest that fluids extravasation may actually be increased during anesthesia [ 20 ]. The increased colloid osmotic pressure of FFP compared with NS may, however, counteract extravasation in the FFP groups with a resulting smaller difference in the hemodynamic response between bolus and slow resuscitation groups.…”
Section: Discussionmentioning
confidence: 99%